O Campo como Laboratório: Relevância das Viagens Didáticas na Formação do Profissional em Lazer e Turismo – Estudo de Meio em Curitiba/PR - Ulian, Flavia (Revista de Graduação USP, 2017)
The report shows the advantages of using fieldwork as a pedagogical practice in undergraduate courses, mainly in the EACH-USP Leisure and Tourism course. It presents a bibliographic review that highlights the benefits of the study of both as a motivating activity in the teaching-learning relationship as well as in the observation practice guided by concepts previously presented in the classroom. It discusses some important requirements in the elaboration of a didactic trip, reporting the trip to Curitiba/PR during the discipline Tourism and Transportation. It also shows testimonials from some of the participants.